Multi-Party Model in Cooperatives : Deep Understanding of Ratio Legis in Minister of Cooperatives Regulation Number 8 of 2021 - Awaliya, Monica; Sukarmi, Sukarmi; Sihabudin, Sihabudin (International Journal of Business, Law, and Education, 2024)
In line with the progress of the global economy, especially in Indonesia, it is recognized that a digitalization and modernization era has taken place, which continues to evolve and never ceases. This necessitates cooperatives to strengthen themselves to be healthier, self-reliant, modern, strong, and competitive, in accordance with cooperative principles, enabling them to play a role as a "pillar of the national economy." In April 2022, the Minister of Cooperatives and Small and Medium Enterprises Regulation on Cooperatives with a Multi-Party Model Number 8 of 2021, hereinafter referred to as "Permenkop UKM KMP," came into effect on October 21, 2021. In other countries, the Multi-Party Model Cooperatives, referred to as "KMP," have been commonly used for various business purposes. For example, they have been established in the United Kingdom since 1870, in the United States since the 1990s, in Italy since 1991, in Canada since 1997, in Portugal since 1998, and in France since 2001. Firdaus Putra, the Chairman of the Indonesian Consortium For Cooperative Innovation (ICCI), mentioned in a webinar on the dissemination of Minister of Cooperatives and SMEs Regulation No. 8 of 2021 concerning Multi-Party Model Cooperatives, that Italy is the best-practice example of KMP globally, with approximately 14,000 KMPs as of today. However, with the issuance of Permenkop UKM KMP in Indonesia, the history of Permenkop UKM KMP began only in 2022, making it a relatively new terminology in Indonesia. The issuance of Minister of Cooperatives and SMEs Regulation Number 8 of 2021 on Cooperatives with a Multi-Party Model raises several questions about the reasons behind the introduction of this new regulation. For instance, is the regulation solely implemented as a UUCK (Job Creation Law) enforcement measure, given the mention of the need for cooperatives to support job creation, even though it is not explicitly explained which type of cooperatives are referred to in the UUCK.